Mapping the interconnections: a systematic review and network analysis of factors influencing teachers' technology acceptance - Galimova, Elvira G.; Oborsky, Alexey Yu.; Khvatova, Maria A.; Astakhov, Dmitry V.; Orlova, Ekaterina V.; Andryushchenko, Irina S. (Frontiers in Education, 2024)
This paper uses the Technology Acceptance Model (TAM) framework to examine elements affecting technology acceptance in teacher education. By means of network and cluster analysis, we investigate the distribution, interactions, and importance of components influencing technology adoption among pre-service and in-service teachers. Following the PRISMA method, a thorough search of Scopus and Web of Science databases produced 32 publications for in-depth study. Key interactions among TAM variables were found using network analysis done in RStudio with the igraph tool. Our results underline in teacher education settings the importance of perceived utility, attitudes toward technology, and perceived ease of use. The study revealed certain topic groups including psychological and social elements, knowledge and occupational relevance, and pragmatic uses in learning environments. While pointing up possible study gaps in this field, the network analysis offers insights into important factors and relationships impacting instructors' technology uptake. This study helps to create efficient professional development programs meant to improve instructors' technological integration skills and enable the successful application of instructional technologies in their respective fields. Our results provide insightful direction for teachers and legislators creating focused initiatives to increase technology acceptance in learning environments.